الروايات الإسرائيلية في تفسير المدرسة العقلية الحديثة: دراسة نقدية تحليلية: Biblical Narratives (al-Israiliyyat) as Reflected in Modernists’ Rationalist School of Tafsir: An Analytical Study - Ilyas Adam, Ibrahim (Afkar: Jurnal Akidah dan Pemikiran Islam, 2017)
This paper analyses the methodology adopted by modern exegetes and rationalists in their school of tafsir in their engagements with al-Israiliyyat (Biblical narratives) and assess the impact of their approach in tafsir. The study focuses on some prominent figures of the rationalists school of tafsir in nineteenth-century Egypt such as Muhammad `Abduh, Rashid Rida and Mahmud Mustafa Maraghi. It critically reviews their arguments vis-à-vis their outright rejection of using Biblical narratives in interpreting the Qur’an regardless of their authenticity. In the exegetical context, al-Israiliyyat, refers to Jewish anecdotes and folklore details influenced by the Judeo-Christian milieu. It represents the exegetical views on specific Qur’anic subject matters integrated into tafsir by converts of both the Jewish and the Christian faiths. This exegetical methodology found its way in to tafsir during the era of tabi`in, (the succecsors of the Prophet’s companions) in the second formative phase of tafsir. In those circumstances, tafsir became more or less complex and understanding the Qur’an appeared increasingly difficult because the overall methodology of interpretation was largely influenced by intellectual and philosophical debates as well as sectarianism and theological disputes. This essentially left negative impact on the traditional mode of tafsir and Islamic thought. This study found that the use of al-Israiliyyat to supplement Qur’anic predominant narratives was sometime necessary but misleading on various scales, as not only biblical materials but also extra scriptural narratives were frequently cited in traditional tafasir. As a result, modern scholars sought to combat this intellectual challenge and offer viable alternative by proposing a new methodological framework for tafsir to understand the Qur’an in a manner that corresponds with modern era and align its teaching to all spheres of life. This formed the basis of rationalists school of tafsir. This paper examines the exegetical methodology of modern exegetes and their rationalist approach and evaluates to what extent it breaks with the tradition of mainstream tafsir. The paper concludes that rationalists have gone too far in rejecting al-Israiliyyat outrightly, and their extreme approach in engagement with al-Israiliyyat lacks objectivity and is full of contradictions and inconsistencies. Indeed, this stems from their methodological flaw and seemingly contradictory attempt to mistakenly or deliberately force their rationalist views into the Qur’an.